Health care of the disadvantaged: chronic obstructive pulmonary disease in later life - Fredrik Nyman (Frontiers Media S.A., 2023)
IntroductionChronic diseases have emerged as the foremost causes of death and disability worldwide. This article employs an ethnographic approach to conduct a gerontological investigation of chronic obstructive pulmonary disease (COPD), the third leading cause of global mortality, trailing only cardiovascular diseases and cancers.MethodsThis study is rooted in an extensive amalgamation of biomedical literature and official epidemiological data. Additionally, it offers enriched insights through an extensive ethnographic research methodology, encompassing ethnographic fieldwork, participant observation, interviews, and focus groups.ResultsThe findings expound that individuals grappling with chronic obstructive pulmonary disease often undergo intricate cognitive and emotional experiences, necessitating holistic solutions that consider psychological processes, contextual factors, and subjective age. These challenges extend beyond the purview of a purely medical perspective.ConclusionThis article concludes that the lens of gerontology is invaluable in comprehending chronic obstructive pulmonary disease, particularly due to its association with old age and increased longevity. Among older individuals, diagnosing the condition presents a formidable challenge. Breathlessness, a cardinal symptom, often overlaps with normal age-related declines in pulmonary function, rendering COPD's insidious onset misconstrued as a consequence of aging-related changes.